Attendance System Based on Face Recognition - Rai, Anjali; Chauhan, Ayushi; Chaudhary, Deepak (International Journal of Computer Sciences and Engineering, 2020)
The Growing Interest of computer vision within the past decade. From a preferred computer vision is an area of research , it has been found that a complex problem of computer vision is rise above by face detection and recognition and it provide us one of the better and successful analysis the image of applications and unable to understand the algorithm. Because of the essential nature of the problem, In area of research computer science and computer vision make use of neuro-scientific and psychological studies. It mainly use for the purpose of processing the computer image that advances in nature and help us to understand the research that provide awareness that how our brain work and vice versa. Many developer have various purpose of making different applications for the users that can be access on different platforms which mainly work to analysis carefully the facial features of the person. This application based on computer vision which is an open source named as Intel’s , OpenCV and framework.